Pandemic of a New Coronavirus Infection (COVID-19): A State-Legal and Economic Phenomenon - Natalia RAKSHA; Anna BORENSTEIN; Elena POZDNYAKOVA; Yulia VETCHINOVA; Sergey LIKHACHEV; Andrey PASHIN (Communications of International Proceedings, 2021)
The article is devoted to the consideration of the Covid-19 pandemic as a socio-legal and economic phenomenon. Theoretical and empirical methods were used in the research process. Today, the problem of pandemics and human vulnerability to certain types of threats is becoming more urgent every day. New foci of diseases appear every day. Now the pandemic is not a problem of one country, but of the whole world as a whole. Events develop in such a way that neither high social status nor financial components can protect against infection. The article examines the approaches of public authorities to the localization of the problem, ways to solve it, the degree of necessity to restrict the constitutional rights of citizens, as well as measures to support the population and business during the pandemic. In the current conditions, the administrative and legal policy pursued by the state is especially important, since the future of the whole world depends on its results.
Keywords: pandemic; new coronavirus infection (COVID-19); state-legal and economic phenomenon; improvement.